Effect of nano curcumin administration on IL-6 expression in placental organs and fetal weight exposed to stress during pregnancy in mice - Viski Fitri Hendrawan; Yudit Oktanella; Habib Syaiful Arif Tuska; Intan Firdha Olien Noor Al Ichsan (Open Veterinary Journal)
Background: Stress can cause an increase in proinflammatory cytokines, IL-6, which plays a role in the inflammatory response and causes changes in the placenta, causing a low risk of the fetus being born. Giving nanocurcumin, which functions as an anti-inflammatory and antioxidant, is expected to reduce cortisol levels which increase during pregnancy.